0345 Insomnia Is Associated With Depression And Anxiety In Japanese City Government Employees. (12th April 2019) - Kadotani, Hiroshi; Takami, Masanori; Nishikawa, Kohei; Sumi, Yukiyoshi; Fujii, Yusuke; Matsuo, Masahiro
Abstract: Introduction: Depression is well known to be associated with insomnia. Anxiety is also known to associated with sleep disorders, but its association with insomnia is not well understood. Here we analyze association between insomnia and anxiety in a Japanese working population. Methods: A cross-sectional questionnaire survey was conducted as a part of epidemiological study named "Night in Japan Home Sleep Monitoring Study (NinJaSleep Study)" in November 2017. Participants were the city government employees in a rural city in Shiga prefecture, Japan. Insomnia, anxiety and depression were analyzed by ISI (insomnia severity index), GAD-7 (Generalized Anxiety Disorder 7) and PHQ-9 (Patient Health Questionnaire 9), respectively. GAD-7≥10 and PHQ-9≥10 were categorized as anxiety and depression, respectively. Results: 1689 responded to the survey (participation rate: 82.1%, male: 38.9%, age: 45.4±12.2 years, BMI: 22.5±3.64, ISI: 7.04±4.41, GAD-7: 3.26±3.91, PHQ-9: 4.71±4.58). 1413, 33, 141, 102 had no anxiety or depression, anxiety only, depression only, and both anxiety and depression, respectively. ISI scores for subjects with no anxiety or depression, anxiety only, depression only, and both anxiety and depression were 6.10±3.68, 9.42±5.26, 11.44±4.37, and 13.38±4.42, respectively (P<0.001). Conclusion: There is high comorbidity of anxiety and depression. Insomnia was associated with both anxiety and depression. ISI was highest when participants had both anxiety and depression. Support (If Any): Supported in part by a research grant from Investigator-Initiated Studies Program of Merck Sharp & Dohme Corp. / MSD K.K. The opinions expressed in this paper are those of the authors and do not necessarily represent those of Merck Sharp & Dohme Corp. / MSD K.K."